(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Increasing population-level physical activity (PA) requires system-level policy action. However, public policies targeting the general population, without addressing socially disadvantaged populations, might unintentionally increase socioeconomic inequities in PA. This is particularly concerning since disadvantaged groups are less likely to meet PA recommendations. This rapid review assesses the evidence on the effects of public policies on equity in PA. Methods: A literature search was performed in seven bibliographic databases up to May 7, 2024, in collaboration with a librarian. Studies were included if they: a) focused on changes in PA behaviour, PA proxies, or the PA environment as outcomes, b) examined public policy as the independent variable, and c) included a low socioeconomic status (SES) (sub)population. Screening was done in duplicate. Key data extracted included: the public policy, target population, and/or SES subgroup measures, PA outcomes and equity-related findings. Policies were grouped into domains aligned with the eight investments from the International Society for Physical Activity and Health and categorised based on their impact on inequities: reducing, increasing, no effect, or mixed effects. Results: Out of 10,350 records screened, 83 studies were included. The results showed that 30% of the public policies reduced inequities, 39% had no effect, 10% increased them, and 21% had mixed effects. Fewest PA policies were identified in the healthcare (n = 2) and workplace (n = 0) domains and the most in the community-wide domain (n = 22). Overall, the education, transport, community-wide, and mass media policy domains showed the greatest potential to reduce inequities in PA and/or to benefit high and low SES populations equally. Policies that most consistently reduced inequities or had a neutral effect on inequities included: a) infrastructure policies, b) financial incentives supporting active transport, c) multi-component school-based PA and health policy programmes, d) school physical education policies, and e) policies supporting mass media campaigns. Conversely, urban design and sport for all policies varied with regards to their effects on inequities. Conclusions: This review identified several types of policies, particularly in the education, transport, community-wide, and mass media domains, with the potential for promoting PA in an equitable way. These findings offer valuable insights for future policymaking. Support/Funding Source: This is part of the project IMPAQT which is funded from Ireland, Health Research Board; Poland, National Centre for Research and Development; Germany, Federal Ministry of Education and Research; The Netherlands, The Netherlands Organisation for Health Research and Development; Romania, Executive Agency for Higher Education, Research, Development and Innovation Funding; Lithuania, Research Council of Lithuania, under the umbrella of the Partnership Fostering a European Research Area for Health (ERA4Health) (GA N° 101095426 of the EU Horizon Europe Research and Innovation Programme). Keywords: Policy, review, physical activity, equity